Pengaruh Store Atmosphere dan Persepsi Harga Terhadap Kepuasan Konsumen dengan Kepercayaan Sebagai Variabel Intervening pada Cafe Dari Sini - Aditya Rivaldo Rais; Vicky Brama Kumbara; Della Asmaria Putri (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to find out how much influence Store Atmosphere and Price Perception on Consumer Trust with Trust as an intervening variable at Cafe Dari Sini. Method collection data through google form and questionnaires, which are distributed as mucl 150 respondents - In this study using the analysis tool structural Equation Modeling (SEM) using the Partial Least Square (PLS) 3.0. The results of this study indicate that Store Atmosphere has a positive and significant effect on consumer satisfaction at Cafe Dari Sini. Price perception has a positive and significant effect on consumer satisfaction at Cafe Dari Sini. Consumer trust has a positive and significant effect on consumer satisfaction at Cafe Dari Sini. Store Atmosphere has a positive and significant effect on consumer satisfaction through consumer trust as an intervening factor at Cafe Dari Sini. And price perception has a positive and significant effect on consumer satisfaction through consumer trust as an intervening factor at Cafe Dari Sini.